Illumination‐Driven Energy Level Realignment at Buried Interfaces between Organic Charge Transport Layers and a Lead Halide Perovskite. Issue 6 (17th February 2022) - Zu, Fengshuo; Roß, Marcel; Frohloff, Lennart; Shin, Dongguen; Tessler, Nir; Albrecht, Steve; Koch, Norbert
Abstract : Tremendous progress in employing metal halide perovskites (MHPs) in a variety of applications, especially in photovoltaics, has been made in the past decade. To unlock the full potential of MHP materials in optoelectronic devices, an improved understanding of the electronic energy level alignment at perovskite‐based interfaces is required. This particularly pertains to such interfaces under device operation conditions, e.g. under illumination with visible light such as in a solar cell. Herein, it is revealed that the energy level alignment at the buried interface between a double cation lead halide perovskite film and charge‐selective organic transport layers changes upon white light illumination. This is found from photoemission experiments performed with the samples in dark and under illumination, and the interfacial energy level shift is reversible. The underlying mechanism is attributed to the accumulation of one charge carrier type within the perovskite film at the interface under illumination, as a result of the charge‐selective nature of the organic layer. The fact that the interfacial energy level alignment at MHP‐based junctions under illumination can differ from that in dark is to be taken into account to fully rationalize device characteristics. Abstract : The energy level alignment at buried interfaces between perovskites and an organic charge transport layer can undergo significant changes under illumination compared to dark. This is caused by selective charge carrier accumulation within the perovskite layer.